A Systematic Review and Meta-analysis of the Factors Associated With Nonadherence and Discontinuation of Statins Among People Aged ≥65 Years. (19th January 2018) - Ofori-Asenso, Richard; Jakhu, Avtar; Curtis, Andrea J; Zomer, Ella; Gambhir, Manoj; Jaana Korhonen, Maarit; Nelson, Mark; Tonkin, Andrew; Liew, Danny; Zoungas, Sophia
Abstract: Background: Older individuals (aged ≥65 years) are commonly prescribed statins but may experience a range of barriers in adhering to therapy. The factors associated with poor statin adherence and/or discontinuation among this population have not been comprehensively reviewed. Methods: We conducted a systematic review to identify English articles published through December 12, 2016 that reported factors associated with nonadherence and/or discontinuation of statins among older persons. Data were pooled via random-effects meta-analysis techniques. Results: Forty-five articles reporting data from more than 1.8 million older statin users from 13 countries were included. The factors associated with increased statin nonadherence were black/non-white race (odds ratio [OR] 1.66, 95% confidence interval [CI] 1.39–1.98), female gender (OR 1.08, 95% CI 1.03–1.13), current smoker (OR 1.12, 95% CI 1.03–1.21), higher copayments (OR 1.38, 95% CI 1.25–1.52), new user (OR 1.58, 95% CI 1.21–2.07), lower number of concurrent cardiovascular medications (OR 1.08, 95% CI 1.06–1.09), primary prevention (OR 1.49, 95% CI 1.40–1.59), having respiratory disorders (OR 1.17, 95% CI 1.12–1.23) or depression (OR 1.11, 95% CI 1.06–1.16), and not having renal disease (OR 1.09, 95% CI 1.04–1.14). The factors associated with increased statin discontinuation were lower income status (OR 1.20, 95% CI 1.06–1.36), current smoker (OR 1.14, 95% CI 1.06–1.23), higher copayment (OR 1.61, 95% CI 1.53–1.70), higher number of medications (OR 1.04, 95% CI 1.01–1.06), presence of dementia (OR 1.18, 95% CI 1.02–1.36), cancer (OR 1.22, 95% CI 1.11–1.33) or respiratory disorders (OR 1.19, 95% CI 1.05–1.34), primary prevention (OR 1.66, 95% CI 1.24–2.22), and not having hypertension (OR 1.13, 95% CI 1.07–1.20) or diabetes (OR 1.09, 95% CI 1.04–1.15). Conclusion: Interventions that target potentially modifiable factors including financial and social barriers, patients' perceptions about disease risk as well as polypharmacy may improve statin use in the older population.